Les nouveaux sondages sur la pratique du breton et celle de l’occitan en Aquitaine - Fañch Broudic (La Bretagne Linguistique, 2010)
Two surveys were carried out a few months apart, one on the practice of the Breton language in Brittany and on the representations linked to it at the end of 2007, the other on the practice of the Occitan language in Aquitaine in November 2008. The two surveys present similarities and differences, both in terms of methodology and results. First of all, the « language » object. If Breton is immediately perceived as a language, the speakers do not identify themselves any less with a specific dialect. In the case of Occitan, half of the speakers refer to it as a patois. While 13% of the people surveyed in Western Brittany state that they can speak Breton, the rate of speakers varies from 3% to 15% depending on the department, with a regional average of 9%. The two surveys show a significant reduction in these rates compared to the surveys conducted ten years earlier.